Visceral leishmaniasis in heart transplant patients in the endemic state of Ceará, Brazil: a report of two casesLeishmaniose visceral em pacientes submetidos a transplante cardíaco no estado do Ceará, área endêmica no Brasil: um relato de dois casos - de Carvalho, Bráulio Matias; Castelo Branco, Debora de Souza Colares Maia; Valdivia, Paulo Alberto Cosquillo; Rocha, Marcos Fábio Gadelha; Brilhante, Raimunda Sâmia Nogueira; de Souza Neto, João David; Vasconcelos, Glauber Gean; Almeida, Germana Porto Linhares; Mejia, Juan Alberto Cosquillo; Bandeira, Tereza de Jesus Pinheiro Gomes; Sidrim, José Júlio Costa (Journal of Health & Biological Sciences, 2016)
Visceral leishmaniasis (VL) in transplant patients is a serious disease, with atypical and aggressive manifestations, compromising patient survival. During the period from 2008 to 2012, 126 heart transplants were performed in the state of Ceará, Brazil, of which, two patients developed VL. Fever, pancytopenia and hepatosplenomegaly were the common clinical signs. Both patients were diagnosed and properly treated, but the first one had a clinical relapse and died, five months after treatment. These findings emphasize the importance of investigating VL in heart-transplant patients in endemic areas and highlight the importance of early diagnosis and treatment for favorable clinical outcomes.